2015
DOI: 10.1039/c5ra05154a
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity and thermal rectification in H-terminated graphene nanoribbons

Abstract: The purpose of this article is to provide a systematic evaluation to perform characteristics on the thermal conductivity and thermal rectification of H-terminated graphene nanoribbons (HGNRs) with Lpristine/LH-terminated = 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…By adjusting the coverage and distribution patterns of hydrogen adsorbates on graphene's edge or surface, significant thermal rectifications can be achieved. [48][49][50] Due to the significant effects of hydrogenation on thermal transport, it is necessary to investigate its impact on the interfacial thermal conductance between phosphorene and graphene. In practice, hydrogen atoms can be attached to the single or both sides of a graphene sheet.…”
Section: Effects Of Hydrogenationmentioning
confidence: 99%
“…By adjusting the coverage and distribution patterns of hydrogen adsorbates on graphene's edge or surface, significant thermal rectifications can be achieved. [48][49][50] Due to the significant effects of hydrogenation on thermal transport, it is necessary to investigate its impact on the interfacial thermal conductance between phosphorene and graphene. In practice, hydrogen atoms can be attached to the single or both sides of a graphene sheet.…”
Section: Effects Of Hydrogenationmentioning
confidence: 99%
“…The simulation study is helpful for us to predict the properties of new materials, so as to better promote our experiments. Previous molecular dynamics simulation studies have shown that the structure, [7,34,[36][37][38][39][40][41][42] thickness, [38,43] defect, [44][45][46][47] doping type, [41,48,49] external stain, [50][51][52] and heterogenous structure [53][54][55][56] of graphene can influence the performance of thermal rectifier. In this section, the molecular dynamics simulation results of previous graphene thermal rectification characteristics are summarized, which will contribute to development of new graphene-based thermal rectifiers.…”
Section: Molecular Dynamics For Graphene-based Thermal Rectifiermentioning
confidence: 99%
“…Y shape 63% 1/2 [38] U shape 104% 1 [37] H shape 33.7%. 1 [42] on the work of the experiments, in which practical thermal rectifier devices were realized. In 2012, Tian et al [40] created a macroscopic scale thermal rectifier based on reduced graphene oxide (GO) with triangular and two-rectangular structure.…”
Section: Shapesmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Recently, it has been reported that the single asymmetric material of reduced graphene oxide (rGO) can produce a heat rectication phenomenon at the macroscopic scale based on the dependencies of thermal conductivity of rGO on temperatures. 9 At the nanoscale, the thermal rectication effect of the different asymmetric structures, including asymmetric carbon nanotubes, 1,5,7,[14][15][16][17][18][19] graphene nanoribbons, 11,[20][21][22][23][24] nanoporous silicon, 25 and graphene, 4,6,9,10,16,26 was studied in-depth, and simulated using molecular dynamics theory and classical nonequilibrium simulation. The abovementioned research studies have shown that the geometric asymmetry was a very valid way to increase the rectication ratio.…”
mentioning
confidence: 99%